Taxonomy of the zodiac loaches, Mesonoemacheilus triangularis, M. tambaraparniensis and M. periyarensis, endemic to the Western Ghats of India (Teleostei: Nemacheilidae) - Anoop, V. K.; Dahanukar, Neelesh; Ali, Anvar; Raghavan, Rajeev (Zootaxa, 2017)
The Nemacheilid loaches, Noemacheilus triangularis tambaraparniensis and Nemacheilus periyarensis have been widely considered to be synonyms of the zodiac loach, Mesonoemacheilus triangularis. An integrative taxonomic investigation based on topotypic material, involving molecular analysis of two mitochondrial genes (cytochrome oxidase subunit 1 and cytochrome b), multivariate morphometric analysis based on non-metric multidimensional scaling and non-parametric multivariate analysis of variance suggests that the three species are in fact distinct.